An Overview of Infections Associated with Urinary Catheters - EV, Rasheeda; KP, Hasna (Journal of Neonatal Surgery, 2025)
A urinary tract infection (UTI) is an infection that can occur anywhere in the urinary system. The urinary system consists of the kidneys, ureters, bladder, and urethra. Most infections affect the lower urinary system, specifically the bladder and urethra. Women are more likely to have a UTI than males. If the infection is localized to the bladder, it can be uncomfortable and irritating. However, major health complications might occur if a UTI spreads to the kidneys. A urinary catheter is a tube that collects urine from the bladder and connects it to a drainage bag. It is somewhat flexible and may be constructed from a variety of materials. A urinary catheter is used when a person's bladder cannot be empty, resulting in kidney pressure or urine incontinence. A health care professional may recommend a urinary catheter for a number of reasons. Biofilms, cooperative communities of microorganisms, commonly form on indwelling urinary catheters, leading to persistent infections that are resistant to standard antimicrobial therapies. Urinary tract infections (UTIs), predominantly caused by uropathogenic bacteria, are increasingly associated with Candida species, particularly in patients with prolonged catheterization. These infections often involve multidrug-resistant strains, complicating treatment and increasing the risk of spreading resistant organisms. Addressing this complex issue requires more than isolated interventions, as it contributes to significant hospital and community-acquired infections..